2018
DOI: 10.1002/ldr.3230
|View full text |Cite
|
Sign up to set email alerts
|

Easily mineralizable carbon in manure‐based biochar added to a soil influences N2O emissions and microbial‐N cycling genes

Abstract: Manure‐based biochar is an effective amendment to increase both carbon sequestration and the fertility of degraded soils, whereas the responses of N2O emissions and microbial‐N cycling genes to its application and the underlying mechanisms are poorly understood. Here, four biochars were produced under two pyrolysis temperatures (300 and 700°C) and with two organic C extraction procedures (water and acetone extraction). The resulting biochars were either with relative enrichment or depletion in easily mineraliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Therefore, biochars at high pyrolysis temperatures can compete for electrons with NO 3 − during denitrification, whereas biochars produced at low pyrolysis temperatures act as electron donors and provide the electrons for NO 3 − reduction. This was also supported by the stimulated N 2 O emission under supply of low-temperature biochar (e.g., 300 °C) (Dai et al 2019) and the inhibited N 2 O emission associated with the application of high-temperature biochar (e.g., 700 °C) (Harter et al 2014(Harter et al , 2016. Although NO 3 − is the substrate for denitrifiers, due to the low content of NO 3 − in biochar and the negative charges in biochar surface, the NO 3 − in biochar does not significantly affect denitrification.…”
Section: Soil Microbial-mediated N Cyclingmentioning
confidence: 70%
See 3 more Smart Citations
“…Therefore, biochars at high pyrolysis temperatures can compete for electrons with NO 3 − during denitrification, whereas biochars produced at low pyrolysis temperatures act as electron donors and provide the electrons for NO 3 − reduction. This was also supported by the stimulated N 2 O emission under supply of low-temperature biochar (e.g., 300 °C) (Dai et al 2019) and the inhibited N 2 O emission associated with the application of high-temperature biochar (e.g., 700 °C) (Harter et al 2014(Harter et al , 2016. Although NO 3 − is the substrate for denitrifiers, due to the low content of NO 3 − in biochar and the negative charges in biochar surface, the NO 3 − in biochar does not significantly affect denitrification.…”
Section: Soil Microbial-mediated N Cyclingmentioning
confidence: 70%
“…Both processes can increase soil denitrification and hence N 2 O emission. Dai et al (2019) showed that biochars with high labile C contents stimulated soil denitrification and had greater stimulatory effects on the abundances for denitrification genes, such as nirK, nirS, and nosZ and also N 2 O emission, compared with biochar with low labile C. The close positive relationships between N 2 O emission and biochar-increased dissolved organic C (Feng et al 2018) and biochar volatile matter (Subedi et al 2016) also indicated the C-N coupled cycling in soil denitrification and N 2 O emission. As the labile C in biochar increased with decreasing pyrolysis temperature, we propose that the biochars produced at low pyrolysis temperatures (e.g., 300 °C) contribute to denitrification and N 2 O emission to a greater extent than those produced at high temperatures.…”
Section: Soil Microbial-mediated N Cyclingmentioning
confidence: 90%
See 2 more Smart Citations
“…Nevertheless, between 1 and 20% of the organic N in manure biochar can be mineralized in the short term and subsequently increase the nitrification rate. Biochars with lower aromaticity also have higher amounts of available C that can increase denitrification rates ( nirK , nirS , and nosZ ) and N 2 O emissions [ 79 ] ( Table 2 ). Additionally, the observed effects are dependent on biochar interactions with soil texture, pH, moisture and soil N [ 100 , 101 ].…”
Section: Effects Of Organic Fertilizers On Nitrifying and Denitrifying Soil Microorganismsmentioning
confidence: 99%